Social medias: Costa Rican remote learning tools in times of COVID-19 - Montenegro Sánchez, Ana Marcela (2022)
Presenté como Ponente Principal "Key note Speaker" en la Conferencia Internacional "Media, Language and Society: Perspectives and Reflections on the Mediatization of Culture" llevada acabo el 10 y 11 de enero del 2022.